Properties of two‐dimensional electron gas in AlGaN/GaN HEMT structures determined by cavity‐enhanced THz optical Hall effect. Issue 5 (14th April 2016) - Armakavicius, Nerijus; Chen, Jr‐Tai; Hofmann, Tino; Knight, Sean; Kühne, Philipp; Nilsson, Daniel; Forsberg, Urban; Janzén, Erik; Darakchieva, Vanya
Abstract: In this work we employ terahertz (THz) ellipsometry to determine two‐dimensional electron gas (2DEG) density, mobility and effective mass in AlGaN/GaN high electron mobility transistor structures grown on 4H‐SiC substrates. The effect of the GaN interface exposure to low‐flow‐rate trimethylaluminum (TMA) on the 2DEG properties is studied. The 2DEG effective mass and sheet density are determined tobe in the range of 0.30‐0.32m0 and 4.3‐5.5×1012 cm –2, respectively. The 2DEG effective mass parameters are found to be higher than the bulk effective mass of GaN, which is discussed in view of 2DEG confinement. It is shown that exposure to TMA flow improves the 2DEG mobility from 2000 cm 2 /Vs to values above 2200 cm 2 /Vs. A record mobility of 2332±61 cm 2 /Vs is determined for the sample with GaN interface exposed to TMA for 30 s. This improvement in mobility is suggested to be due to AlGaN/GaN interface sharpening causing the reduction of interface roughness scattering of electrons in the 2DEG. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)